2009
DOI: 10.1007/s00428-009-0733-y
|View full text |Cite
|
Sign up to set email alerts
|

Congenital granular cell epulis presents an immunohistochemical profile that distinguishes it from the granular cell tumor of the adult

Abstract: Congenital granular cell epulis (CGCE), a rare benign lesion arising from the mucosa of the alveolar ridges of the jaws in newborns, has a clinical course characterized by lack of further growth after birth. Histomorphologically, it resembles a granular cell tumor (GCT) of the adult. The histogenesis of this lesion is unclear. We submitted a series of five CGCEs to a large panel of antibodies in order to trace the origin of the constituent granular cells. The resultant immunohistochemical profile showed positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
83
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 40 publications
7
83
0
Order By: Relevance
“…6 Concerning its uncertain histogenesis, odontogenic epithelium, fibroblasts, 7 Langerhans cells or histiocytes, 8 smooth muscle, nerve-related cells, 9 endothelial cells, pericytes, myofibroblasts, and undifferentiated mesenchymal cells 10 have been implicated in the pathogenesis of CEN, which, however, remains undefined. 11 Microscopically, CEN is composed of sheets of large to medium-sized, round to polyhedral cells that have a discrete cellular membrane, abundant granular cytoplasm, and a single darkly staining nucleus with an eccentrically positioned nucleolus. The covering epithelium is thin and attenuated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Concerning its uncertain histogenesis, odontogenic epithelium, fibroblasts, 7 Langerhans cells or histiocytes, 8 smooth muscle, nerve-related cells, 9 endothelial cells, pericytes, myofibroblasts, and undifferentiated mesenchymal cells 10 have been implicated in the pathogenesis of CEN, which, however, remains undefined. 11 Microscopically, CEN is composed of sheets of large to medium-sized, round to polyhedral cells that have a discrete cellular membrane, abundant granular cytoplasm, and a single darkly staining nucleus with an eccentrically positioned nucleolus. The covering epithelium is thin and attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Such cells are, moreover, strongly positive for acid phosphatase. [9][10][11]13 Slootweg et al 14 concluded that peanut lectin binding protein might be considered a common feature of granular cells regardless of their histogenesis. Lysosomes are supposed to represent the intracellular binding sites for this marker.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported to occur primarily in neonates, and more in females. [9] This suggests a hormonal mechanism in the aetiology. Some studies have shown no evidence of either oestrogen or progesterone receptors, and as such suggest an alternative histogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown no evidence of either oestrogen or progesterone receptors, and as such suggest an alternative histogenesis. [6,7] Vered et al [9] in their review of 33 lesions concluded that the immunohistochemical profile does not implicate any specific cell types for the histogenetic origin of the benign lesion. There has not been any reported case of recurrence after excision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation